Design and Analysis of In-Field Liner (IFL) and IFL Pulling Head for Underwater Pipeline - Muhammad Hazwan Bin Desa, Muhammad Hazwan (Universiti Teknologi Petronas, 2012)
In-Field Liner (IFL) is generally a flexible composite liner pipe, where it is commonly used nowadays to replace the degraded oil and gas steel pipeline. This project is aimed to determine the feasibility and the capability of IFL pipe to sustain the force exerted by the pulling cable in the pulling process to replace the degraded underwater steel pipeline for oil and gas application. There are two main concerns for this project, which are to design a pulling head for IFL pipe and analysis of the IFL pipe in term if its reaction to a certain amount of pulling force used in the pulling process. For design purposes, CATIA V5R20 software is used whereas ANSYS v14.0 software is used for analysis and simulation purposes. The pulling head design is created using CATIA software according to the specifications of IFL pipe, so that the pulling head will fit properly on the IFL pipe when it is attached. For analysis of IFL pipe, the Finite Element Analysis (FEA) model of IFL pipe in its folded configuration (U-shaped form) will be simulated using ANSYS software in order to determine the ability of IFL pipe to withstand the pulling force exerted by the pulling cable and its reaction to the pulling load will be the priority of this project as this will determine the relevancy and the feasibility of the replacement process by pulling the IFL pipe through the inner side the degraded steel pipeline